The Favorable Effect of Mesenchymal Stem Cell Treatment on the Antioxidant Protective Mechanism in the Corneal Epithelium and Renewal of Corneal Optical Properties Changed after Alkali Burns - Cejka, Cestmir; Holan, Vladimir; Trosan, Peter; Zajicova, Alena; Javorkova, Eliska; Cejkova, Jitka (Oxidative medicine and cellular longevity, 2016)
The aim of this study was to examine whether mesenchymal stem cells (MSCs) and/or corneal limbal epithelial stem cells (LSCs) influence restoration of an antioxidant protective mechanism in the corneal epithelium and renewal of corneal optical properties changed after alkali burns. The injured rabbit corneas (with 0.25 N NaOH) were untreated or treated with nanofiber scaffolds free of stem cells, with nanofiber scaffolds seeded with bone marrow MSCs (BM-MSCs), with adipose tissue MSCs (Ad-MSCs), or with LSCs. On day 15 following the injury, after BM-MSCs or LSCs nanofiber treatment (less after Ad-MSCs treatment) the expression of antioxidant enzymes was restored in the regenerated corneal epithelium and the expressions of matrix metalloproteinase 9 (MMP9), inducible nitric oxide synthase (iNOS), α-smooth muscle actin (α-SMA), transforming growth factor-β1 (TGF-β1), and vascular endothelial factor (VEGF) were low. The central corneal thickness (taken as an index of corneal hydration) increased after the injury and returned to levels before the injury. In injured untreated corneas the epithelium was absent and numerous cells revealed the expressions of iNOS, MMP9, α-SMA, TGF-β1, and VEGF. In conclusion, stem cell treatment accelerated regeneration of the corneal epithelium, restored the antioxidant protective mechanism, and renewed corneal optical properties.
Keywords: buněčná diferenciace; Nitric Oxide Synthase Type II; tukové buňky; Rabbits; Animals; rohovkový epitel; superoxiddismutasa; Immunohistochemistry; antioxidancia; Gene Expression Regulation; Female; Vascular Endothelial Growth Factor A; mezenchymální kmenové buňky; Transforming Growth Factor beta; Epithelium, Corneal; Antioxidants; Corneal Opacity; ženské pohlaví; regulace genové exprese; transplantace mezenchymálních kmenových buněk; zákal rohovky; synthasa oxidu dusnatého, typ II; ochranné látky; Burns, Chemical; Mesenchymal Stem Cell Transplantation; Cell Differentiation; Limbus Corneae; Adipocytes; matrixová metaloproteinasa 9; chemické popálení; zvířata; Protective Agents; Corneal Pachymetry; transformující růstový faktor beta; limbus corneae; Mesenchymal Stem Cells; imunohistochemie; Superoxide Dismutase; alkálie; Alkalies; Matrix Metalloproteinase 9; vaskulární endoteliální růstový faktor A; králíci; pachymetrie rohovky